EXTENSIN18 is required for full male fertility as well as normal vegetative growth in Arabidopsis - Choudhary, Pratibha; Saha, Prasenjit; Ray, Tui; Tang, Yuhong; Yang, David; Cannon, Maura C. (Frontiers in Plant Science, 2015)
EXTENSINS (EXTs) are a 65-member subfamily of hydroxyproline-rich glycoproteins (HRGP) of which 20 putatively form crosslinking networks in the cell wall. These 20 classical EXTs are involved at the start of new wall assembly as evidenced by a requirement for EXT3 during cytokinesis, and the ability of some EXTs to polymerize in vitro into dendritic patterns. EXT3 was previously shown to form pulcherosine (3 Tyrosines), cross-links. Little direct data exists on the other 19 classical EXTs. Here we describe the phenotypes of ext18 mutants and rescued progeny as well as associated expression profiles of all 20 classical EXT genes. We found that EXT18 is required for full male fertility, as well as for normal vegetative growth. EXT18 has potential to form crosslinking networks via di-iso-di-tyrosine (4 Tyrosines) covalent bonds, and not via pulcherosine –due to deficit of lone Tyrosines. This together with ext18 defective pollen grains and pollen tubes, and reduced plant size, suggests that EXT18-type EXTs are important contributors to wall integrity, in pollen and other rapidly extending walls. The data also show that a knockout of EXT18 had a pleiotropic affect on the expression of several EXTs, as did the reintroduction of the native EXT18 gene, thus supporting the thesis that transcription of groups of EXTs are co-regulated and work in different combinations to make distinctive inputs into wall assembly of different cell types. These insights contribute to basic knowledge of cell wall self-assembly in different cell types, and potentially enable biotechnological advances in biomass increase and plant fertility control.